Resepsi Sosial Dan Makna Spiritualitas Dalam Tradisi Mengaji Di Kuburan: Fenomenologi Masyarakat Desa Bangai: Social Reception and the Meaning of Spirituality in the Tradition of Studying in Graves: Phenomenology of Bangai Village Society - Rizki Ramadhan Sitepu; Ilhamni Ilhamni; Bilfahmi Putra (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
Contemporary Muslim engagements with the Qur’an manifest in various ways. In scholarly discussions, this phenomenon is referred to as the Living Qur'an—how humans engage with and interpret the Qur'an as both a text and a source of significance. An such is the custom in Bangai Village, where individuals read the Qur’an at graves for three consecutive days and nights following a death. This practice is founded on the conviction that the recitations advantage the deceased and demonstrate profound spiritual and social consciousness. This study examines the significance and progression of this tradition. Data were gathered through observations and interviews with key informants using a qualitative descriptive method in field research. The research employs Alfred Schutz's phenomenological theory to comprehend the underlying significances of the activity. The results are categorized into three principal domains. The subjective meanings encompass spiritual and social qualities, whereas the objective meaning emphasizes its educational function. The motivations for the custom are dual: the cause motive indicates its perceived positivity and use in everyday life, while the objective motive pertains to enhancing comprehension of Islamic teachings and promoting fraternity. The reciting tradition adheres to a distinct structure of pre-procession, procession, and post-procession stages, each characterized by particular rites and significance. This study demonstrates the embodiment of the Living Qur’an within local tradition, integrating spirituality, education, and communal cohesion into a significant religious practice.